If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2s(5s + -7) + -1s(7s + 6) = 0 Reorder the terms: 2s(-7 + 5s) + -1s(7s + 6) = 0 (-7 * 2s + 5s * 2s) + -1s(7s + 6) = 0 (-14s + 10s2) + -1s(7s + 6) = 0 Reorder the terms: -14s + 10s2 + -1s(6 + 7s) = 0 -14s + 10s2 + (6 * -1s + 7s * -1s) = 0 -14s + 10s2 + (-6s + -7s2) = 0 Reorder the terms: -14s + -6s + 10s2 + -7s2 = 0 Combine like terms: -14s + -6s = -20s -20s + 10s2 + -7s2 = 0 Combine like terms: 10s2 + -7s2 = 3s2 -20s + 3s2 = 0 Solving -20s + 3s2 = 0 Solving for variable 's'. Factor out the Greatest Common Factor (GCF), 's'. s(-20 + 3s) = 0Subproblem 1
Set the factor 's' equal to zero and attempt to solve: Simplifying s = 0 Solving s = 0 Move all terms containing s to the left, all other terms to the right. Simplifying s = 0Subproblem 2
Set the factor '(-20 + 3s)' equal to zero and attempt to solve: Simplifying -20 + 3s = 0 Solving -20 + 3s = 0 Move all terms containing s to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 3s = 0 + 20 Combine like terms: -20 + 20 = 0 0 + 3s = 0 + 20 3s = 0 + 20 Combine like terms: 0 + 20 = 20 3s = 20 Divide each side by '3'. s = 6.666666667 Simplifying s = 6.666666667Solution
s = {0, 6.666666667}
| x+5-10=1 | | -4(x+5)-42=7-33 | | x^2=14x-16 | | -6(x+3)-18=11+1 | | 93-(6x-10)=6(x+3)+x | | 14-1=5 | | 12z^2-28z+11= | | f(x)=9x^2+3x+3 | | 5x+2x-4=45 | | 5x^2+6x+1=42 | | -25(10+x)=25x+250 | | 0.25+0.05n=0.05+0.1n | | 5x-2(3x-7)=3(2x-9)+7x | | 4+3(x+9)=22 | | 30=9X+2-5X | | -2w+48=7(w+3) | | 18=x+125 | | 5y^2+75y-170= | | 0.55p=9.9 | | -2y^2-6y=-2 | | (2sinx-1)(cosx+1)= | | 18=9x+2-5x | | 0.4x+0.8=3.6 | | 240x+0.25=387.50 | | 5x=21x+28 | | 2.4=6.5+y | | 34+(-3)(12)= | | 3x-5(x-4)=-8+4x-20 | | 2x-15+4x=4(3x-6)+6 | | 8x+3=8x-4x | | 11-y=6 | | 4g+2(-8+5g)=1-g |